Updated evidence of the Naoshuantong capsule against ischemic stroke: a systematic review and meta-analysis of randomized controlled trials - Que, Cuilin; Wei, Yupeng; Yin, Guanxiang; Zhou, Congren; Liu, Zhenhong; Lai, Xinxing; Qin, Mingzhen; Xiong, Xuejiao; Zheng, Xiangyi; Dong, Xinglu; Gao, Ying (Frontiers in Pharmacology, 2024)
Background: Stroke is a serious health issue that can result in death or disability, leading to a significant economic strain on society and families. A growing number of studies has shown that Naoshuantong capsule (NSTC) is beneficial as a treatment for ischemic stroke (IS) in recent years.Our study aims to provide an update on the safety and efficacy of NSTC in IS patients.We thoroughly searched eight databases to identify suitable randomized controlled trials (RCTs) assessing the effectiveness of NSTC in the treatment of IS. The National Institute of Health Stroke Scale (NIHSS) for acute period and modified Rankin scale (mRS) at 3 months for non-acute period were considered as primary outcome, and secondary outcomes included NIHSS for non-acute period, mRS, Barthel Index (BI), Modified Barthel Index (MBI), Stroke-specific Quality of life (SS-QOL) and the recurrence rate of cerebrovascular events. Subsequently, its quality was assessed using the Cochrane Risk Assessment Scale Statistical analysis was conducted using RevMan 5.3 and Stata 14.0.Results: A total of 27 RCTs were included which involved 3139 patients. The results showed that NSTC improved neurological function not only in the acute period (MD = -2.53; 95%CI: -2.91, -2.15; P < 0.00001) but also in the non-acute period (MD = -3.70; 95%CI: -5.82, -1.58; P = 0.0006) and improved the long-term functional outcomes with lower mRS scores MD =-0.68; 95%CI: -1.09, -0.26; P = 0.001). At the same time, The NSTC decreased the risk of cerebrovascular disease recurrence (RR = 0.43, 95%CI: 0.27, 0.70; P = 0.0006), and increased quality of life in the acute period (MD =23.88; 95%CI: 16.63, 31.13; P < 0.00001). Significant disparities in the incidence of adverse events between the NSTC and control groups were not observed. The certainty of evidence was estimated as moderate to very low.: NSTC emerges as a potentially efficacious and safe treatment option for IS. NSTC could improve neurological function in different period of IS, and it has certain clinical value in secondary prevention. As a result of the poor quality and heterogeneity of the included trials, larger and standardized RCTs are needed to validate NSTC in IS treatment.